2019
DOI: 10.7717/peerj.6295
|View full text |Cite
|
Sign up to set email alerts
|

The use of one-stage meta-analytic method based on individual participant data for binary adverse events under the rule of three: a simulation study

Abstract: ObjectiveIn evidence synthesis practice, dealing with binary rare adverse events (AEs) is a challenging problem. The pooled estimates for rare AEs through traditional inverse variance (IV), Mantel-Haenszel (MH), and Yusuf-Peto (Peto) methods are suboptimal, as the biases tend to be large. We proposed the “one-stage” approach based on multilevel variance component logistic regression (MVCL) to handle this problem.MethodsWe used simulations to generate trials of individual participant data (IPD) with a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…An advantage of the Peto OR for such studies is that it does not need a continuity correction to estimate the relative effect and variance. Several simulation studies have shown it to be a more robust effect estimator than the classic OR with continuity correction when the events are rare [15, 28, 32]. We, however, demonstrated no advantage for the Peto ORs in the situation of rare events with large studies; indeed it may lead to less conservative error estimation.…”
Section: Discussionmentioning
confidence: 60%
“…An advantage of the Peto OR for such studies is that it does not need a continuity correction to estimate the relative effect and variance. Several simulation studies have shown it to be a more robust effect estimator than the classic OR with continuity correction when the events are rare [15, 28, 32]. We, however, demonstrated no advantage for the Peto ORs in the situation of rare events with large studies; indeed it may lead to less conservative error estimation.…”
Section: Discussionmentioning
confidence: 60%
“…These three were actually the most commonly used methods for rare events in practice. The Peto's OR and MH methods generally perform better than the continuity correction [19,28]. However, the Peto's OR could be only used to deal with studies with single-armed zero-events; for studies with both-arm zero-events, most software programs would remove such studies directly [26].…”
Section: Discussionmentioning
confidence: 99%
“…We concentrate here on MAs of study-level summaries, which is far more common in the assessment of adverse events, though patient-level analysis is to be preferred when data are available. 3 The methods used when performing MAs of binary data are frequently done using the standard inversevariance fixed-effects model which is based on large-sample normal approximation, or fixed-effects methods based on exact distributional theory such as the Mantel-Haenszel (MH) 4 or Peto model, 5 or the standard random-effects DerSimonian-Laird (DL) model. 6 Because these methods lack power to investigate the incidence of rare events and are mostly based on large sample normal approximation particularly inverse-variance, 7,8 their statistical properties for estimating treatment effects are often judged as suboptimal either through results being biased, confidence intervals being inappropriately wide or statistical power being too low to detect any true differences.…”
Section: Introductionmentioning
confidence: 99%
“…We concentrate here on MAs of study-level summaries, which is far more common in the assessment of adverse events, though patient-level analysis is to be preferred when data are available. 3…”
Section: Introductionmentioning
confidence: 99%